Kannan-Type Contractions on New Extended b-Metric Spaces. (13th September 2021) - Aydi, Hassen; Aslam, Muhammad; Sagheer, Dur-e-Shehwar; Batul, Samina; Ali, Rashid; Ameer, Eskandar
Abstract : This article is focused on the generalization of some fixed point theorems with Kannan-type contractions in the setting of new extended b -metric spaces. An idea of asymptotic regularity has been incorporated to achieve the new results. As an application, the existence of a solution of the Fredholm-type integral equation is presented.